African Perspectives of Research in Teaching & Learning 2 (1): (2018) - Wadesango, Newman editor in chief (My University, 2018)
Refer to the document
APORTAL journal
APORTAL completed issue 2 (1): (2018)
Keywords: Higher education; Teaching and learning; Global warming; Capitalism; Educational research; Poetic inquiry; Teaching history; Kreol languages; Multilingual education; Internationalization; Global warming; Education -- Study and teaching; Multilingual education; Hegemony; History -- Study and teaching; Globalization; Morisyen language